Dampak Perceived Quality Terhadap Brand Loyalty: Peran Mediasi Brand Trust Dan Brand Image - Farid Ardyansyah; Samuel PD Anantadjaya; Irma M Nawangwulan; Timotius A Rachmat; Agus Supriyanto (Optimal: Jurnal Ekonomi dan Kewirausahaan, 2022)
This study aims to determine the effect of perceived quality on brand image, brand trust and brand loyalty, the effect of brand image and brand trust on brand loyalty, and the effect of the relationship between perceived quality on brand loyalty mediated by brand image and brand trust. The method in this study is to use a type of quantitative research method. This study serves to prove the relationship between research variables. Data analysis techniques were performed using Structural Equation Modeling with AMOS version 25.0. The research sample is bakery consumers in Kudus Regency as many as 172 respondents. This study obtained the results that perceived quality has an effect on brand image, brand trust, and brand loyalty, brand image and brand trust have a significant effect on brand loyalty, and brand image and brand trust mediate perceived quality on brand loyalty. This research provides managerial implications in the form of the importance of maintaining and increasing perceived quality through brand trust and brand image to meet consumer satisfaction so as to create brand loyalty.